Kupffer's vesicle size threshold for robust left–right patterning of the zebrafish embryo. Issue 1 (3rd November 2015) - Gokey, Jason J.; Ji, Yongchang; Tay, Hwee Goon; Litts, Bridget; Amack, Jeffrey D.
Abstract : Background: Motile cilia in the "organ of asymmetry" create directional fluid flows that are vital for left–right (LR) asymmetric patterning of vertebrate embryos. Organ function often depends on tightly regulated organ size control, but the role of organ of asymmetry size in LR patterning has remained unknown. Observations of the organ of asymmetry in the zebrafish, called Kupffer's vesicle (KV), have suggested significant variations in KV size in wild‐type embryos, raising questions about the impact of KV organ size on LR patterning. Results: To understand the relationship between organ of asymmetry size and its function, we characterized variations in KV at several developmental stages and in several different zebrafish strains. We found that the number of KV cilia and the size of the KV lumen were highly variable, whereas the length of KV cilia showed less variation. These variabilities were similar among different genetic backgrounds. By specifically modulating KV size and analyzing individual embryos, we identified a size threshold that is necessary for KV function. Conclusions: Together these results indicate the KV organ of asymmetry size is not tightly controlled during development, but rather must only exceed a threshold to direct robust LR patterning of the zebrafish embryo. Developmental Dynamics 245:22–33, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Kupffer's vesicle (KV) development is variable in wild‐type populations. The amount of KV variability is similar among different genetic backgrounds. Cilia elongation is independent of KV lumen size. KV must exceed a size threshold to direct robust LR patterning of the zebrafish embryo.